Review Journal of Political Philosophy, Volume 8.1. - Wisnewski, Jeremy (Newcastle upon Tyne : Cambridge Scholars Pub., 2010)
The Review Journal of Political Philosophy publishes high-quality work in moral and political philosophy, broadly-construed. The Journal prides itself on its eclecticism, not limiting itself to any particular tradition, school of thought, or historical period. We publish articles, reviews, and discussion pieces from leading and new scholars from analytic and continental perspectives, along with articles that bridge the gap between these traditions.
Table of contents; acknowledgments; machiavelli's method revisited; the skeptical anarchist; does political liberalism make sense?; why is (claiming) ignorance of the law no excuse?; a politics in the absence of a universal human nature; "diligence is the mother of good fortune"; phenomenology, interrogation and biopower.
Print version record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: Philosophy; Political science -- Philosophy; Philosophie; philosophy; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Philosophy; Political science -- Philosophy